Development and feasibility of a sex- and gender-sensitive primary care intervention for patients with chronic non-cancer pain receiving long-term opioid therapy (GESCO): a study protocol - Christine Kersting; Johannes Just; Alexandra Piotrowski; Alexandra Schmidt; Neele Kufeld; Rebecca Bisplinghoff; Michaela Maas; Veronika Bencheva; Jordan Preuß; Birgitt Wiese; Klaus Weckbecker; Achim Mortsiefer; et al. (Pilot and Feasibility Studies)
Abstract Background Chronic non-cancer pain (CNCP) is a common condition worldwide. The disease burden is influenced not only by pain itself, but also by psychiatric co-morbidities, which aggravate symptoms, generally negatively influence therapies, and may thereby lead to frustration, resignation, or withdrawal. A growing body of evidence suggests that sex and gender aspects influence CNCP management as the experience of pain, the emotions associated with it, and the expression of pain may differ between women and men. In addition, doctor-patient communication is known to be influenced by gender stereotypes. Despite there being evidence on such differences, current guidelines do not consider sex- and gender-sensitive approaches. In order to examine how to adequately address the diversity of the experience and processing of pain in patients of differing sex and gender, the GESCO study aims at developing and pilot testing a sex- and gender-sensitive intervention for patients with CNCP receiving long-term opioid therapy (LTOT) in primary care. Methods The development process is designed in accordance with the first two phases of the UK Medical Research Council. Phase I will iteratively explore, develop, and pilot the intervention’s modules using literature searches, interviews, and workshops involving stakeholders and experts. Phase II will pilot-test the novel intervention in a sample of 40 patients with CNCP under LTOT from ten general practices using an effectiveness-implementation hybrid design including a mixed-methods process evaluation focusing on implementation strategy criteria and a single-arm, pre-post comparison to determine preliminary effects in preparation for a larger effectiveness trial. The intervention will combine in-person educational sessions for general practitioners and tools to be used in patient care. Discussion The intervention aims to improve CNCP management in primary care by empowering practitioners to reflect on their attitudes towards pain and stereotypes. Besides sex and gender aspects, awareness of other factors that might affect the care process, such as age, social conditions, or culture, is also promoted. The intention is to develop a comprehensive care concept for CNCP that considers aspects relevant for sex- and gender-sensitive care which are transferrable to other health care fields as well. Trial registration German Clinical Trial Register DRKS00029980.